Proposed Business Strategy for Inditex Global - Mukmin Qowiy, Ismail; Hudrasyah, Herry (The Indonesian Journal of Business Administration, 2016)
Abstract - Rising prosperity and a spread of wealth have given a huge and expanding market for textiles and clothing industry. Market are expanding and so the competition. Inditex as a leader in the industry seek this opportunity to increase its standing among the top player of this industry. With its â€œfast fashionâ€ model, Inditex has been performed exceptionally well, proofed by its huge channel of 1,700 stores in 86 countries leaving behind its main rival like GAP and H&M. However the success not last long. Contrast with rapid expansion several years before, in 2013 annual sales report Inditex began showing sign of slowdown. For the last few years, company has been aimed to find new source of profit due to shrinking growth. The aim of this study is to find out the root cause behind the slowdown and to formulate the strategy to tackle the problem and enhance the growth of Inditex. This study is divided into four chapters. The first chapter talks about the outlines of the research background and highlight the objective of the study. Chapter two talk about business issue and the analysis of business environment. Chapter three provides the business solution alternatives. Last chapter discusses the application and practice of the solution. It highlights the execution of the business strategy on four aspect; marketing, finance, research & development (R&D), and management information system. This chapter also presents the conclusion of the main findings. Â Keyword: Business strategy, Fast fashion, Growth slowdown, Business Expansion, Apparel industry